Supply Chain Operations in the Arctic : Implications for Social Sustainability - Tsvetkova, Antonina (Taylor & Francis, 2023)
The extant corpus of research on supply chain sustainability in the Arctic exhibits a conspicuous neglect of the social dimension, rendering it the most underprivileged among the three pillars of sustainability. A deep dive into the Arctic, this edited volume endeavors to fill this opulent lacuna by placing the unjustly forsaken concept of social sustainability at the forefront of supply chain management (SCM) research. By showcasing real-life case studies of supply chain operations, all in different industries and located in various Arctic regions, this book delves into the intricate interplay between business interests, political ambitions, and social issues. In response to the burgeoning demand for more in-depth empirical studies within the SCM landscape, it offers a compelling tapestry of experiences and candid views on the complexities of implementing socially sustainable and responsible policies in Arctic supply chains. Featuring contributions by 26 esteemed scholars worldwide, this collection proffers 13 thought-provoking and insightful chapters, arranged in a logical and coherent sequence that enables readers to follow a clear thread of argumentation. With abundant theoretical insights and empirical data, Supply Chain Operations in the Arctic: Implications for Social Sustainability will appeal to a wide range of readers keeping a close eye on Arctic operations and sustainable issues. It is a timely and essential resource for students and scholars of SCM and sustainability studies, as well as businesses, policymakers, Indigenous Peoples, and non-governmental organizations seeking to promote socially responsible supply chain practices in the Arctic.